Influencing factors of hand, foot, and mouth disease based on structural equation modeling in Hubei, China - Wuwei Wang; Dacai Deng; Shengsheng Gong; Hongying Chen; Long Hu (Scientific Reports)
Abstract Hand, foot and mouth disease (HFMD) is a major public health issue in Hubei Province; however, research on the direct and indirect effects of factors affecting HFMD is limited. This study employed structural equation modeling (SEM) and geographically weighted regression (GWR) to investigate the various impacts and spatial variations in the factors influencing the HFMD epidemic in Hubei Province from 2016 to 2018. The results indicated that (1) with respect to the direct effects, the number of primary school students had the greatest positive direct effect on the number of HFMD cases, with a coefficient of 0.542. Socioeconomic factors strongly influence HFMD cases more directly than natural factors. (2) Concerning indirect effects, the minimum temperature, combined with the per capita disposable income of urban residents, had the greatest positive indirect effect on HFMD cases, with a coefficient of 0.022. Both natural and social factors had more substantial direct impacts on the HFMD epidemic than indirect impacts. (3) Regarding total effects, the number of primary school students, through various natural and social factors, had a total effect coefficient of 0.503 on HFMD incidence. (4) The number of primary school students, per capita GDP, and the number of hospital beds per thousand people had the most significant spatial impacts on HFMD cases. In underdeveloped regions, the HFMD epidemic is more heavily influenced by economic factors.